The Influence of Integrity, Code of Ethics, Competence and Independence of Government Internal Auditors on the Quality of Audit Reports at the Regional Inspectorate of Empat Lawang Regency - Agung Kurniawan; Nisma Aprini; Delvina Yulanda (Universitas Dehasen Bengkulu, 2026)
The author's research aimed to determine and analyze the influence of integrity, code of ethics, competence, and independence of internal government supervisory officers, both individually and collectively, on the quality of audit reports at the Empat Lawang Regency Inspectorate. The research method employed was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis employed descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial and simultaneous tests, and coefficients of determination. The results showed that integrity, code of ethics, competence, and independence of internal government supervisory officers positive influenced the quality of audit reports individually at the Empat Lawang Regency Inspectorate. Integrity, code of ethics, competence, and independence of internal government supervisory officers positive influenced the quality of audit reports at the Empat Lawang Regency Inspectorate.